An observational study of individual child journeys through autism diagnostic pathways, and associated costs, in the UK National Health Service - Male, Ian; Farr, William; Bremner, Stephen; Gage, Heather; Williams, Peter; Gowling, Emma; Honey, Emma; Gain, Aaron; Parr, Jeremy (Frontiers in Rehabilitation Sciences, 2023)
Background Demand for diagnostic assessment in children with possible autism has recently increased significantly. Services are under pressure to deliver timely and high-quality diagnosis, following National Institute and Care Excellence multidisciplinary assessment guidelines. This UK National Health Service study aimed to answer: how many hours of health professional time are required to deliver autism diagnostic assessment, and how much does this cost?. Method Case notes of 20 children (1–16 yrs.) from 27 NHS trusts, assessed through an autism diagnostic pathway in the previous year, were examined retrospectively. Data included: hours of professional time, diagnostic outcome. Assessment costs calculated using standardised NHS tariffs. Results 488 children (aged 21–195 months, mean 82.9 months, SD 39.36) from 22 Child Development Services (CDS), four Child and Adolescent Mental Health Services (CAMHS) and one tertiary centre; 87% were either under 5 (36%) or 5 to 11 years (51%). Children seen by CDS were younger than CAMHS (mean (SD) 6.10 (2.72) vs. 10.39 (2.97) years, p < 0.001). Mean days to diagnosis were 375 (SD 235), with large variation (range 41–1553 days). Mean hours of professional time per child was 11.50 (SD 7.03) and varied substantially between services and individuals. Mean cost of assessment was £846.00 (SD 536.31). 339 (70.0%) children received autism diagnosis with or without comorbidity; 54 (11%) received no neurodevelopmental diagnosis; 91 (19%) received alternative neurodevelopmental diagnoses. Children with one or more coexisting conditions took longer to diagnose, and assessment was more costly, on average 117 days longer, costing £180 more than a child with no neurodevelopmental diagnosis. Age did not predict days to diagnosis or assessment costs. Conclusion Typical assessment took 11 h of professional time and over 12-months to complete, costing GB£850 per child. Variation between centres and children reflect differences in practice and complexity of diagnostic presentation. These results give information to those delivering/planning autism assessments using multi-disciplinary team approach, in publicly funded health systems. Planning of future diagnostic services needs to consider growing demand, the need for streamlining, enabling context appropriate services, and child/family complexity.